Late Neogene Lophophaenidae (Nassellaria, Radiolaria) from the eastern equatorial Pacific - Trubovitz, Sarah; Renaudie, Johan; Lazarus, David; Noble, Paula (Zootaxa, 2022)
Lophophaenidae is a clade of polycystine radiolarians that was highly abundant and diverse in the Late Neogene–Recent eastern equatorial Pacific (EEP). Despite their importance in fossil plankton assemblages, lophophaenids have been neglected because of their generally small size, complex morphology, and weak taxonomic framework. These challenges have left many lophophaenid concepts poorly defined or lacking formal description. Here we address this with a review of 101 lophophaenid taxa observed in EEP Middle Miocene–Recent marine sediments. We discuss existing lophophaenid genera Amphiplecta Haeckel 1881, Arachnocorallium Haeckel 1887, Arachnocorys Haeckel 1860, Botryopera Haeckel 1887, Ceratocyrtis Bütschli 1882, Lithomelissa Ehrenberg 1847, Lophophaena Ehrenberg 1847, and Peromelissa Haeckel 1881, including full species lists. We describe Pelagomanes n. gen., 23 new species: ​​Amphiplecta kikimorae n. sp., Arachnocorys jorogumoae n. sp., Botryopera amabie n. sp., Botryopera babayagae n. sp., Botryopera bolotniki n. sp., Ceratocyrtis? chimii n. sp., Ceratocyrtis vila n. sp., Lithomelissa alkonost n. sp., Lithomelissa babai n. sp., Lithomelissa dybbuki n. sp., Lithomelissa sirin n. sp., Lophophaena arie n. sp., Lophophaena casperi n. sp., Lophophaena domovoi n. sp., Lophophaena gozui n. sp., Lophophaena ikiryo n. sp., Lophophaena ikota n. sp., Lophophaena kaonashii n. sp., Lophophaena leshii n. sp., Lophophaena rusalkae n. sp., Lophophaena shishigae n. sp., Lophophaena ushionii n. sp., and Pelagomanes ibburi n. sp., and one new subspecies, Arachnocorys pentacantha wanii n. subsp. In addition, we document 35 taxa in open nomenclature, and revise generic assignments of 10 species. The names of 32 previously-described species are upheld, but with clarified synonymies, discussion, and illustrations. This work contributes a practical framework for identifying tropical Late Neogene–Recent lophophaenid taxa, and demonstrates their rich morphological diversity.